The corpulent phenotype—how the brain maximizes survival in stressful environments - Peters, Achim; Kubera, Britta; Hubold, Christian; Langemann, Dirk (Frontiers in Neuroscience, 2013)
The reactivity of the stress system may change during the life course. In many - but not all - humans the stress reactivity decreases, once the individual is chronically exposed to a stressful and unsafe environment (e.g. poverty, work with high demands, unhappy martial relationship). Such an adaptation is referred to as habituation. Stress habituation allows alleviating the burden of chronic stress, particularly cardiovascular morbidity and mortality. Interestingly, two recent experiments demonstrated low stress reactivity during a mental or psychosocial challenge in subjects with a high body mass. The corpulent subjects were also found to display a robust brain energy metabolism during stress. In this focused review we attempt to integrate these experimental findings in a larger context. Are these data compatible with data sets showing a prolonged life expectancy in corpulent people? From the perspective of neuroenergetics, we here raise the question whether ‚obesity’ is unhealthy at all. Is the corpulent phenotype possibly the result of ‚adaptive phenotypic plasticity’ allowing optimized survival in stressful environments?